The right to self-representation and its challenges to the administration of fair trial at the International Criminal Tribunal for the Former Yugoslavia : lessons for the International Criminal Court - Hansungule, Michelo (University of Pretoria, 2015)
Dissertation (LLM)--University of Pretoria, 2013.